Concepts in biochemistry - Boyer, Rodney F. ([S.l.] : Brooks/Cole Pub Co, 2001)
This book reflects the modern tendency of biochemical studies and experimental design to be more heavily based on the nucleic acids and genetic approaches. Boyer enhances student's understanding of biological processes by initiating the study of biochemistry with nucleic acids (especially DNA) playing a more central role and treating other biomolecules as direct or indirect products. Boyer's lively presentation captures students' interest, gives them a current and practical sense of biochemistry, and presents applications that they can use in their careers and everyday lives. An accompanying interactive CD-ROM/Web site provides additional opportunities for study and enrichment. Boyer includes all the topical coverage usually provided in current biochemistry courses, but modifies the sense of focus and balance of coverage. The result is a text of exceptional relevance for students in allied-health fields, agricultural studies, and related programs.
Keywords: biochemistry